Availability and spatial variability of copper, iron, manganese and zinc in soils of the State of Ceará, Brazil (Revista Ciência Agronômica, 2018)
The aim of the present work was to: (i) determine and map the micronutrient content (copper - Cu, iron - Fe,manganese - Mn and zinc - Zn) in soils of the State of Ceará; (ii) evaluate soil attributes related to micronutrient availability;and (iii) evaluate, by ordinary kriging, the spatial dependence of the micronutrient content. The study area is located in thecentral region of Ceará, in the basin of the River Banabuiú. Soil samples were collected in the surface and subsurface layers todetermine the chemical attributes, granulometry, and micronutrient content, extracted with Mehlich-1 solution. The sites of theprincipal types of soil in the region were spatialised and the results submitted to descriptive analysis and Pearson correlationanalysis. The semivariograms with the best fit were tested using the ordinary kriging method, and the maps of spatial variabilitywere prepared. The highest values for the mean, maximum and minimum levels of Cu and Fe are found in the subsurface layers,while for Mn and Zn, they are found in the surface layers. In the surface layers, the majority of soils present Fe, Mn and Zn inlevels suitable for agricultural production, while the levels of Cu are classified as medium to low. The micronutrients showeda significant positive correlation, especially with the soil attributes and with each other. Cu, Fe, Mn and Zn are classified ashaving medium to strong spatial dependence in the surface and subsurface layers.